Analysis of the reasons for low mean time between failures of pumping equipment at a high-viscosity permo-carbon oil deposit - D. A. Ivanov (Наука. Инновации. Технологии, 2024)
Sucker-rod pumping unit in operation after huff and puff cyclic steam injection operates in a wide range of rheological properties of fluids and medium temperatures. During the initial stage after steam injection, hot liquid fluids are extracted with a temperature of about 200°C and a viscosity of several tens of cP. During this period, all injected water is also pumped out of the reservoir, which entered the reservoir in the form of steam during steam injection phase. After several months of operation, after the bottom-hole zone cools down, the viscosity of the oil increases to several hundred cP. The influence of stable emulsions on the properties of fluids also increases. These changes lead to increased loads and torque on pumping equipment during operation, which leads to premature failures. The challenge to secure long-term operations with a high mean time between failures of pumping units is critical and demanding. The analysis of the main causes and trends of low mean time between failure using a large array of information and data was performed. Certain big data analysis approaches have been developed and presented and used to formulated qualitative and quantitative conclusions and recommendations. The field uses the same type of pumping equipment with only a change in the diameter of the plunger depending on the flow rate. Based on the results of the analysis, the area of the field was identified where it is necessary to make significant changes in the pump parameters due to the increased viscosity of the oil. In such conditions according to world practice longer stroke sucker-rod pumping unit is used reducing the number of strokes, increasing mean time between failure. Experience in similar fields in other regions of the world also indicates the need to use machine learning to improve pump performance.